Three‐dimensional mixture simulations of flow over dynamic rippled beds. Issue 3 (28th March 2013) - Penko, A.M.; Calantoni, J.; Rodriguez‐Abudo, S.; Foster, D.L.; Slinn, D.N.
Abstract : [1] A three‐dimensional mixture theory model for flow and sediment transport in the seafloor boundary layer, SedMix3D, simulated the flow over and the resulting sediment entrainment and evolution of rippled beds. SedMix3D treats the fluid‐sediment mixture as a continuum of varying density and viscosity with the concentration of sediment and velocity of the mixture simulated by the Navier‐Stokes equations coupled with a sediment flux equation for the mixture. Model validation was performed by comparing simulated time‐dependent flow quantities and bulk flow statistics with measurements obtained in the laboratory under scaled forcing conditions. Two‐dimensional planes extracted from a three‐dimensional simulation were compared to observations made using planar Particle Image Velocimetry (PIV) in a laboratory flume. The simulated results of time‐averaged velocities and time‐dependent quantities of vorticity and swirling strength were in good agreement with the observations. The model was used to analyze the three‐dimensionality of vortex formation and ejection produced by oscillatory flow over vortex ripples, a process that cannot be observed in the laboratory with planar PIV measurements. The three‐dimensional simulated results showed that the swirling strength varied significantly in the cross‐flow direction, indicating that the vortices formed and dissipated non‐uniformly due to random fluctuations. Subsequently, an order of magnitude difference in offshore sediment flux was observed using two different methods to calculate sediment fluxes (spatially averaging and at a point). The results suggest that while a two‐dimensional plane may be sufficient to examine the general hydrodynamics over ripples, three‐dimensional analysis is necessary for a complete understanding of sediment transport. Key Points: SedMix3D is a 3D mixture theory model simulating flow over bedforms. 3D simulated flow results agreed well with 2D laboratory observations. Simulation exhibits cross-flow variation of vorticity and suspended sediment.